DAMPAK POHON PENAUNG YANG BERBEDA TERHADAP PERTUMBUHAN TANAMAN KOPI - Sihotang, Yosep Prada Agung; Kusumawati, Anna (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2024)
Basically, there are still many coffee farmers who don't know the benefits of planting shade plants, and don't know which types of shade plants are effective to plant to support coffee productivity. This research aims to determine the effect of shade plants on the vegetative growth of coffee plants. The research method used is RAK 1 factor, namely the type of shade plant for coffee plants, with two levels, namely sengon and mahogany shade plants. The parameters observed include the amount of litter, nitrogen (N) and carbon (C) content of the litter, nutrients N, Phosphorus (P), Potassium (K) in the soil, vegetative growth of coffee plants and microclimate (temperature, humidity and intensity of sunlight ). The collected data was analyzed using a T-test at 5% level and a correlation test. The results showed that there were no real differences in temperature and humidity in the two shelters, but there were real differences in light intensity. Plant height and diameter of coffee plants did not show significantly different results due to different shading, but the primary branches and secondary branches of coffee plants under the shade of sengon had significantly higher yields than coffee under the shade of mahogany. The amount of litter per week under the shade of sengon was greater and significantly different than under the shade of mahogany. The N and C content in sengon plant litter is higher than mahogany plant litter. Temperature has a correlation with humidity and light intensity and coffee stem diameter has a strong correlation with the primary and secondary branches of coffee plants. The soil N and P content under the shade of sengon plants was higher than under the shade of mahogany. Choosing the right shade plants greatly influences the plants cultivated.